Developing general English program syllabus - Windri Kusuma Dewi (Journal of English Language and Pedagogy, 2019)
This study aims at developing a syllabus for General English Conversation of English Care course. The method of this study used R & D method. It was because the result of the research is used to design a product. The findings of this research show that the content of the syllabus is General English. The content was gained from the result of need analysis. It was gained from the existing documents such as the textbook, list of teaching material, and the main goal. Syllabus has an important role for teachers in teaching learning process it covers objectives, learning activities and task, topic, themes, and vocabularies. If a teacher does not have a syllabus, it will be difficult for her/him to plan her/his teaching learning process. Planning a syllabus is one activity that will help teachers and learners of general English to achieve their successful learning goals. A syllabus is needed by teachers because it gives the lesson a framework, an overall shape. By having a syllabus, teachers will know what should be done and what should be achieved in the class and at the end of the class. Therefore, teachers will not deviate from the objectives which have been established before. Moreover, a syllabus reminds teachers what they have intended to do in the class, particularly if they are distracted by other things in the class. Syllabus will help them directly go back to the plans previously written in syllabus.